(untitled) (Journal of Nepal Geological Society, 1998)
Groundwater recharge estimate is an essential part of the management of the water resources. The Terai plain of Nepal with multi-aquifer system and a number of river systems need thorough understanding on their interconnection. Groundwater samples from the dugwells, shallow tube wells, deep tube wells, and river water were analysed for major chemical constituents. The chemistry of confined aquifer system is found to be different from the unconfined aquifers. The groundwater recharge to the confined aquifers is therefore believed to be not by vertical infiltration from the shallow aquifers but directly from the palaeo and present river beds. Estimation of groundwater recharge in parts of the Terai plain by rainfall factor warrants rethinking.